Pengaruh Jenis Media Tanam Dan Jenis Nutrisi Terhadap Pertumbuhan dan Hasil Tanaman Seledri (Apium graveolens L.) Varietas Amigo Pada Hidroponik Sistem Wick - Sutinah, Sutinah; Syah, Bastaman; Sugiono, Darso (JURNAL AGROPLASMA, 2023)
Celery is a group of leafy vegetables that has many benefits. Efforts to cultivate urban plants are increasingly difficult. This is due to land conversion that is occurring on a large scale from agricultural land to residential and industrial areas. Therefore we need other alternatives for farming which can be done in narrow and limited land, one of which is by using a hydroponic cultivation system. The purpose of this study was to obtain the type of planting media and nutrient solution that gave the highest yield growth for celery (Apium graveolens L.) Amigo varieties in the hydroponic wick system. This research was conducted at the Taiwan Technichal Mission (TTM) Greenhouse located on Jl. Tanjungpura Circle, Karangpawitan, Kec. West Karawang., Karawang, West Java 41315. This research was conducted from March to April 2023. The research method used was an experimental method using a factorial Randomized Block Design (RBD), which consisted of 9 treatments repeated 3 times. The first factor is the planting medium consists of 3 levels, namely m1 (cocopeat), m2 (hydroton) and m3 (rockwool). The second factor consisted of 3 levels, namely n0 (AB mix), n1 (POC of rabbit urine) and n2 (NPK pearl + gandasil-d). The results showed that there was no interaction effect between the types of growing media and the types of nutrients. However, there is an independent influence between the type of growing media and the type of nutrition. In the treatment of rockwool growing media (m3) it was able to give the highest yield of plant height, number of leaves and leaf area. In the treatment of the type of nutrition AB mix (n0) gave the highest results on leaf area, fresh weight per plot and yield of fresh weight per plant.Â Keywords: growing media, celery, nutrition